2004
DOI: 10.1534/genetics.103.024398
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Quantitative Trait Loci Interactions From the Maternal and Offspring Genomes

Abstract: The expression of most developmental or behavioral traits involves complex interactions between quantitative trait loci (QTL) from the maternal and offspring genomes. The maternal-offspring interactions play a pivotal role in shaping the direction and rate of evolution in terms of their substantial contribution to quantitative genetic (co)variation. To study the genetics and evolution of maternal-offspring interactions, a unifying statistical framework that embraces both the direct and indirect genetic effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…False positive QTL(s) could be eliminated by model selection, while higher power and more accurate estimation of QTL effects could be achieved, benefiting from smaller and more accurate estimation of the residual effects because of background control. It should be noted that we have integrated the maternal genome into the model in addition to the offspring genome (Foolad and Jones, 1992;Cui et al, 2004;Hu and Xu, 2005;Wen and Wu, 2007), based on the view that development of embryo/endosperm traits partially depends on its own maternal plant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…False positive QTL(s) could be eliminated by model selection, while higher power and more accurate estimation of QTL effects could be achieved, benefiting from smaller and more accurate estimation of the residual effects because of background control. It should be noted that we have integrated the maternal genome into the model in addition to the offspring genome (Foolad and Jones, 1992;Cui et al, 2004;Hu and Xu, 2005;Wen and Wu, 2007), based on the view that development of embryo/endosperm traits partially depends on its own maternal plant.…”
Section: Discussionmentioning
confidence: 99%
“…It is well evidenced that additive and/or epistatic maternal effects, embryo effects, endosperm effects and gene-environment interaction effects are involved in the genetic development and evolution of crop seed (Zhang et al, 1999;Shi et al, 2000;Cui et al, 2004;Cui and Wu, 2005a,b;Cui et al, 2006). A considerable body of genetic models and statistical methods have been developed and applied to the analysis of real data.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing recognition of the importance of epistasis in complex traits, it is appealing to develop a statistical model that integrates maternal and offspring genome into one mapping framework for dissecting the genetic networks of seed traits. General epistasis is defined as the interaction of two genes at different loci of the same genome; however, some studies have indicated that two epistatic genes can reside in different genomes (Cui et al 2004;Cui and Wu 2005a, b). Zhang et al (2004) proposed a statistical model for testing and estimating the effects of maternal-offspring genome interactions on embryo and endosperm traits during seed development in autogamous plants.…”
mentioning
confidence: 99%
“…This approach can detect epistasis from different genomes, but at the price of ignoring maternal effects of a single QTL. Cui et al (2004;Cui and Wu 2005a,b) proposed a statistical method to detect the genetic mechanism of maternal-offspring genome interactions. Under the assumption that genetic expression of endosperm traits is controlled by both the maternal and the offspring genomes, the method can estimate the direct (offspring) effect, the indirect (maternal) effect, and the effects of maternal-offspring genome interaction simultaneously.…”
mentioning
confidence: 99%
See 1 more Smart Citation